2016
DOI: 10.1007/s11682-016-9661-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional dedifferentiation and reduced task-related deactivations underlie the age-related decline of prospective memory

Abstract: Prospective memory (PM) refers to the ability to remember to execute an intention at the appropriate moment in the future, which can be performed either at the appearance of an event (event-based, EBPM) or after a certain amount of time (time-based, TBPM). PM is generally impaired during aging but the cerebral substrates of this decline have been little investigated. Using functional Magnetic Resonance Imaging (fMRI), we investigated the neural bases of PM in 20 young and 20 healthy older adults. They were pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 52 publications
3
18
0
Order By: Relevance
“…However, a more recent study demonstrated that smaller hippocampus size is significantly associated with lower performance in episodic memory, working memory, processing speed, and executive function tasks 102 . Similarly to motor function, it has been shown that older adults recruit additional brain regions during memory tasks [103][104][105] .…”
Section: Modification Of Brain Functions During Agingmentioning
confidence: 99%
“…However, a more recent study demonstrated that smaller hippocampus size is significantly associated with lower performance in episodic memory, working memory, processing speed, and executive function tasks 102 . Similarly to motor function, it has been shown that older adults recruit additional brain regions during memory tasks [103][104][105] .…”
Section: Modification Of Brain Functions During Agingmentioning
confidence: 99%
“…Here we provide evidence for such dedifferentiation in women the absence of sex differences or deficits in episodic memory performance. Performance-independent dedifferentiation has also been revealed in healthy older adults during prospective memory tasks (Gonneaud et al, 2017). Dedifferentiation can therefore occur independently of performance changes, and may instead reflect a fundamental neurocognitive shift in approach to cognitive tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Here we provide evidence for such dedifferentiation in women the absence of sex differences or deficits in episodic memory performance. Performance-independent dedifferentiation has also been revealed in healthy older adults during prospective memory tasks (Gonneaud et al, 2017).…”
Section: Sex Differences Inmentioning
confidence: 98%
“…We expected to observe an effect of age on PM, especially the prospective component that is subserved by executive processes and frontal areas [43,44]. We further expected this effect to be more pronounced for TB intentions than EB ones [45][46][47]. We also hypothesized that sleep would preferentially reinforce the retrospective component of intentions, which is mainly hippocampus-dependent [48].…”
Section: Introductionmentioning
confidence: 94%